PENINGKATAN KEPEDULIAN STAKEHOLDER PEMBANGUNAN DALAM MENCEGAH STUNTING DI DESA CANGKUANG WETAN KECAMATAN DAYEUHKOLOT KABUPATEN BANDUNG - Ida Widianingsih; Budhi Gunawan; Binahayati Rusyidi (Universitas Padjadjaran, 2018)
This article describes the efforts of increasing the awareness of the development stakeholders at the village level in order to prevent stunting in Cangkuang Wetan Village, Dayeuhkolot Sub District, Bandung Regency as a form of community service that has been integrated with the research of Unpad lecturers and also Unpad Students. Stunting is a national strategic issue that can be observed in many regions of Indonesia, which in turn pushes the goverment to implement prevention efforts. This article mainly uses the qualitative research method with many participatory techniques, which include observations, interviews, FGD's, and socialization. The activities was around 7 months long and started with field research preparation, issue mapping, activity planning, and socialization of the importance of stopping stunting to the Village Development Stakeholders. The team found that the Village Apparatus, the locals that work at the Posyandu, mothers of Balita, and also the Balita were very active and enthusiastic during the socialization process. However, there are still many obstacles in the efforts to prevent stunting that should be overcome through a more comprehensive and integrated with the development plan of the village in order to achieve a more optimal result.